Prediksi Financial Distress Menggunakan Rasio Keuangan, Sensitivitas Makroekonomi, dan Intellectual Capital - Oktarina, Dian (Ultimaccounting Jurnal Ilmu Akuntansi, 2018)
This study examine the effect of financial ratio, macroeconomic indicator, and intellectual capital on financial distress. Financial ratio measured by debt to equity ratio, total assets turnover ratio, current ratio, quick ratio, working capital ratio, net income to total assets ratio, and cash ratio. Macroeconomic indicator that used in this research were lending rate, Consumer Price Index (CPI), IHSG, inflation, and exchange rate IDR/USD. Value Added Intellectual Coefficient (VAIC) measured by proxy Intellectual capital. Sample of this research were manufacturing company listed in IDX during 2012-2016. This research used logistic regression method for testing hypothesis. The result of this research showed that, inflation, exchange rate IDR/USD, total assets turnover ratio, and net income to total assets ratio is significantly negative with the financial distress. It implied that if the inflation, exchange rate IDR/USD, total assets turnover ratio, and net income to total assets ratio is high then financial distress is low.